Sorptivity and chloride permeability of concrete using ferronickel slag as fine aggregate - Saha, A.; Sarker, Prabir (2017)
Abstract: Molten ferronickel slag (FNS) is a by-product of the production process of ferronickel alloy. The granulated FNS is broadly supplied by the producers for using it as an alternative fine aggregate in concrete. The present study evaluates some durability properties of concrete using FNS obtained from the smelting of garnierite nickel ore found in New Caledonia. Concrete specimens were prepared by replacing natural sand by FNS aggregate at the rates of 0%, 50% and 100%. The durability properties of concrete were evaluated by conducting the sorptivity test and rapid chloride penetration test (RCPT). The effect of FNS aggregates in concrete containing 30% class F fly ash as a cement replacement was also determined. It was found that sorptivity and RCPT both increased with the increase of FNS as replacement of natural sand. However, the sorptivity values for concrete with 50% FNS remained within the allowable limit of 0.21 mm/min½ according to a report published by Cement, Concrete and Aggregates Australia. Furthermore, the RCPT values were within the moderate category for these mixtures according to ASTM C 1202-12. On the other hand, use of 30% class F fly ash as cement replacement improved the durability properties of concrete in all three groups. Therefore, the FNS aggregate and class F fly ash can be combined together to produce concrete utilising substantial amounts of recycled materials in order to reduce the pressure on natural resources caused by the rising demand for concrete.